CRIMINAL LAW ENFORCEMENT THROUGH THE PERSPECTIVE OF COMMUNITY JUSTICE: THEORETICAL ANALYSIS AND PRACTICAL IMPLEMENTATION - Yahman, Dr. Yahman (jfpublisher, 2024)
The enforcement of law in Indonesia has become less equitable these days. Law enforcement tends to ignore justice, whereas justice should be a basic and legal reality. The judiciary as the main institution in law enforcement will lose its function when the law is perceived as an institution that can be manipulated, commercialized, and some legal experts have referred to it as the territory of the jurisdictional mafia. The jurisdictional mafia protects itself by referring to legal supremacy. However, in order to achieve the rule of law, justice and utility are compromised. This research aims to identfy the theoretical analysis and practical implementation of criminal law enforcement through the perspective of community justice. This research used normative methods, with a conceptual and statutory approach. The result indicated that there is a crisis in the implementation of justice, especially in the implementation of law enforcement, due to the existence of an invalid paradigm among those who enforce the law. In addition, the law enforcement officials, especially judges, tend only implement the law in a literal manner. Furthermore, law enforcement apparatus has not completely comprehended that the main purpose of equitable law enforcement is to create law to realize human welfare and harmony.